The Relationship Between Job Satisfaction and Employee Performance in Injection Houseware - Stefanus Lalu Toyo (Jurnal Neo Konseling, 2021)
The purpose of this study is to determine the significance between job satisfaction and employee performance at PT. National ideals. This study resulted in a correlation coefficient (r) of 0.436 ** and with a value of p (probability) = 0.001 & lt; 0.05. This means that there is a significant relationship between job satisfaction and the performance of employees of the injection housekeeping division of PT. National ideals. From these results it can be interpreted that the relationship between job satisfaction and employee performance has a unidirectional relationship. In other words, if one of the variables has increased, the other variables will be strengthened. In the context of this study, job satisfaction has a unidirectional relationship. If the employee's performance has increased and is more strengthened, the employee's performance will be strengthened. So it can be concluded that the hypothesis of this study is that there is a significant relationship between job satisfaction and employee performance of the injection houseware operator at PT. National ideals.